2013
DOI: 10.1038/ejcn.2012.200
|View full text |Cite
|
Sign up to set email alerts
|

Infant feeding patterns over the first year of life: influence of family characteristics

Abstract: Not only maternal education level and age, but also parity and region are important contributors to the variability in patterns. Further studies are needed to describe associations between these patterns and infant growth and later food preferences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
82
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(94 citation statements)
references
References 45 publications
9
82
1
2
Order By: Relevance
“…Similar findings of the influence of maternal education or SEP were observed in studies assessing both meeting feeding guidelines (e.g. appropriate age of solids introduction) and child dietary patterns from the USA [91][92][93], Canada [94,95], UK [96,97], France [98], Australia [99], Brazil [100] and Peru [101]. A 2009 review of the determinants of early weaning and the introduction of cow's milk in infants found strong evidence for a relationship with low levels of both maternal education and SEP [102].…”
Section: Weaning/early-life Dietsupporting
confidence: 78%
“…Similar findings of the influence of maternal education or SEP were observed in studies assessing both meeting feeding guidelines (e.g. appropriate age of solids introduction) and child dietary patterns from the USA [91][92][93], Canada [94,95], UK [96,97], France [98], Australia [99], Brazil [100] and Peru [101]. A 2009 review of the determinants of early weaning and the introduction of cow's milk in infants found strong evidence for a relationship with low levels of both maternal education and SEP [102].…”
Section: Weaning/early-life Dietsupporting
confidence: 78%
“…Perceptions of commercial infant food as convenient and preparation of home-made food as laborious have previously been reported in focus group studies in other European countries [27]. More recently, Betoko et al [12] reported that increased use of ready-prepared vegetables and fruit purees was explained by an awareness of nutritional advice about infant feeding, but a lack of time and culinary skills to implement the advice. However it must also be noted that qualitative studies of contrasting weaning approaches, namely baby-led weaning, also report it to be simple, convenient and to require less meal preparation [8,24].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the United States (US), it has been reported that 73-95% of infants between 4-12 months consume commercially produced baby foods [11]. Usage of these products may be influenced by maternal age, method of feeding, presence of other children in the household, region and food availability [12]. Data from the UK has noted that differences exist according to maternal occupational status and ethnicity [10].…”
Section: Introductionmentioning
confidence: 99%
“…A study to look at the pattern of infant feeding in mothers who have children aged 1 year in EDEN, delayed introduction of additional food and the use of instant baby food is more common in women with a high income. 42 Poverty status associated with the ability to support mothers on child feeding. 43 This research is aligned with other previous studies, where the income of the parents influenced parental in parenting, including feeding practices.…”
mentioning
confidence: 99%